The impact of social media on building long-term relationships with the customers - Jovevski, Dimitar; Vasilevski, Mihail (Journal of Sustainable Development - Integrated Business Faculty, 2019)
One of the main goals of every company is to be profitable. The modern marketing conception positively ties the financial performance of the company with consumer retention, and one of the best ways to retain consumers is by building longterm relationships with them. Social media, used as a marketing channel can significantly help and facilitate communication between them and their customers. Every business, in order to be successful and profitable, must focus on communication and building long-lasting relationships with its consumers. Today it easy to achieve this relationship by using social media. This paper focuses on examining the impact social media have on the process of building long-term relationships with consumers, and aims to offer recommendations that will enable companies to better use social media with their consumers. A descriptive, one-time, individual research was conducted using the method of examination and the application of a deliberate sample. Research has shown that social media definitely have an impact on the process of building long-term relationships and businesses should undoubtedly include and use social media more widely among other tools. Companies should focus their efforts on building long-term relationships through social media to younger consumers, also companies should have to have a more humane attitude towards their consumers and they should try to overcome their expectations on social media. As a result from the research it is shown that companies should be use social media in combination with other traditional methods of building long-lasting relationships
Keywords: Social media, Long-term relationships, CRM, Internet Marketing